Correction: Al-Ahmad et al. Biodentine Inhibits the Initial Microbial Adhesion of Oral Microbiota In Vivo. Antibiotics 2023, 12, 4 - Ali Al-Ahmad; Michael Haendel; Markus Joerg Altenburger; Lamprini Karygianni; Elmar Hellwig; Karl Thomas Wrbas; Kirstin Vach; Christian Tennert (Antibiotics)
We would like to update the readership about the procedure that led to the correction of [...]